2000
DOI: 10.1177/0146167200264001
|View full text |Cite
|
Sign up to set email alerts
|

How Important is the Perception of Personal Control? Studies of Early Stage Breast Cancer Patients

Abstract: Two models of cognitive determinants of distress under adversity were tested in the experiences of two samples of newly treated breast cancer patients (n s = 144 and 202). One model emphasizes the role of perceptions of personal control in subjective well-being; the other model emphasizes expectancies of the occurrence of desired outcomes. In this research, the outcome addressed was remaining free of cancer in the future. In these two samples, beliefs about control over remaining free of cancer played no role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 53 publications
7
62
1
3
Order By: Relevance
“…The level of Helplessness/Hopelessness was also related to quality of life. Similar results can be found in the literature [4]. Negative relations between quality of life and depression, anxiety, helplessness/hopelessness and confusion were found [39], which are also similar to our findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The level of Helplessness/Hopelessness was also related to quality of life. Similar results can be found in the literature [4]. Negative relations between quality of life and depression, anxiety, helplessness/hopelessness and confusion were found [39], which are also similar to our findings.…”
Section: Discussionsupporting
confidence: 93%
“…The reported quality-of-life level was fairly good but not excellent (mean=7.1; SD=2.7 from a maximum of 10), thus suggesting that differences could be explained with a regression analysis The first multiple regression analysis showed that the general severity index (GSI) was the most important predictor of quality of life and explained 21.2% of the variance of quality of life, whereas Helplessness/ Hopelessness predicted 5.5% of the quality of life variance. This correlation between quality of life and distress is often described in the literature [i.e., 1,2,4,15,19], but in this study, the association was not very high. A possible explanation for this only moderate relation between quality of life and general severity is that this sample of breast cancer patients was in remission with an excellent health Therefore, all scales of the BSI instead of the GSI were used as predictors in the second regression analysis.…”
Section: Discussioncontrasting
confidence: 48%
“…It appeared that more control resulted in more information being sought about how to prevent the future problem. This finding does corroborate with the result that has been put forward by Carver et al (2000) that, in order to be able to undertake effective measures, it is important to have the confidence that desired outcomes will be achieved. Control only has an effect when positive results are expected.…”
Section: Discussionsupporting
confidence: 84%
“…Mastery, which is the extent to which people feel in control of the forces that affect their lives [18], has been found to be negatively associated with functional decline [19]. Self-efficacy refers to the confidence people have in being able to execute actions that are required to deal with particular situations [20,21] and appears to be related to the effectiveness of rehabilitation [22]. Furthermore, self-efficacy has been associated with stopping smoking [14], adherence to medication [23] and to physical exercise [13], all important factors in the management of COPD [1].…”
Section: Introductionmentioning
confidence: 99%